2019
DOI: 10.1186/s12913-019-4592-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety climate, safety climate strength, and length of stay in the NICU

Abstract: BackgroundSafety climate is an important marker of patient safety attitudes within health care units, but the significance of intra-unit variation of safety climate perceptions (safety climate strength) is poorly understood. This study sought to examine the standard safety climate measure (percent positive response (PPR)) and safety climate strength in relation to length of stay (LOS) of very low birth weight (VLBW) infants within California neonatal intensive care units (NICUs).MethodsObservational study of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…A factor reduction using EFA led to the identification of OCS, supervisory commitment to safety, TOS, employee engagement to safety and HSE compliance as the dimensions of safety climate. These findings complement the results of previous studies that identified safety climate and perception of process safety as employee engagement to safety, employee safety performance and safe working environment (Mazrouei et al , 2019; Probst, 2015; Roughton et al , 2019; Tawfik et al , 2019). Our findings are in line with Griffin and Curcuruto (2016) and Naik (2019), who found that safety climate is a shared concept which results from individuals’ shared insights and observations of different ways that safety is valued in the organization.…”
Section: Discussionsupporting
confidence: 87%
“…A factor reduction using EFA led to the identification of OCS, supervisory commitment to safety, TOS, employee engagement to safety and HSE compliance as the dimensions of safety climate. These findings complement the results of previous studies that identified safety climate and perception of process safety as employee engagement to safety, employee safety performance and safe working environment (Mazrouei et al , 2019; Probst, 2015; Roughton et al , 2019; Tawfik et al , 2019). Our findings are in line with Griffin and Curcuruto (2016) and Naik (2019), who found that safety climate is a shared concept which results from individuals’ shared insights and observations of different ways that safety is valued in the organization.…”
Section: Discussionsupporting
confidence: 87%
“…As such, the benchmarking of the safety climate within healthcare facilities is now a focus, especially in developed countries that include the United Kingdom, USA, etc. [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This study found that nurse who are working at surgical department has the lowest score of patient safety culture. Surgical departments, including operating rooms, anesthesia units, obstetrics and gynecology departments, and other surgical units, are high hazard settings with a high potential for patient harm [28]. Over half of all hospitals, adverse events (34.35 to 83%) occur in surgical settings [29].The safety culture in these departments has been measured in certain studies.…”
Section: Discussionmentioning
confidence: 99%